THE EFFECT OF SOCIAL MEDIA MARKETING ON CONSUMER AWARENESS ON STARBUCKS PRODUCTS - Dede Suleman; Ida Zuniarti; Sri Rusiyati; Joko Ariawan; Roy Irawan; Helmy Ivan Taruna; Eulin Karlina (ZILLZELL MEDIA PRIMA, 2023)
The purpose of this research is to analyze the influence of social media marketing variables on consumer awareness at Starbucks. This research is explanatory research with a quantitative approach. The data for this study were obtained from 119 respondents. The sampling method in this study is quota sampling. According to multiple regression analysis, the results show that brand exposure has an influence but not significant on consumer awareness, indicated by a t-test value of 0.137 and a significance value of 0.891. Customer involvement has a significant influence on consumer awareness, indicated by a t test value of 2.251 and a significance value of 0.026. Word of Mouth has a significant influence on consumer awareness, indicated by a t test value of 5.172 and a significance value of 0.000.